DETERMINANTS OF TAXPAYER COMPLIANCE AMONG E-COMMERCE MICRO, SMALL, AND MEDIUM ENTEPRISES IN JAKARTA - Devi Damayanti; Indra Pahala; Nuramalia Hasanah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2026)
This study examines the effects of tax understanding, perceived tax fairness, tax awareness, and tax sanctions on taxpayer compliance among e-commerce Micro, Small, and Medium Enterprises in Jakarta, motivated by a sharp decline in Annual Tax Return compliance among non-employee individual taxpayers. Using a quantitative survey method with purposive sampling, 172 valid responses were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that tax sanctions are the strongest determinant of compliance, followed by tax awareness and tax understanding, while perceived tax fairness shows no significant effect; together, the four variables explain a substantial proportion of the variance in taxpayer compliance. These findings extend Compliance Theory to the context of e-commerce Micro, Small, and Medium Enterprises under a turnover-based final tax scheme and indicate that enforcement and awareness based approaches may be more strongly associated with compliance than fairness perceptions in this setting, a pattern that should be interpreted with caution given the cross-sectional design of the study. The findings offer practical implications for tax authorities and related institutions in designing compliance strategies for the growing e-commerce MSME sector.